A Hydrochemical Study of Groundwater Salinization in Qinzhou Bay, Guangxi, Southern China. Issue 3 (1st March 2023) - Hu, Kaiyan; Huang, Qinghua; Han, Peng; Han, Zhiwei; Yang, Zhentao; Luo, Qiang; Li, Peng; Miao, Miao; Zeng, Zhiyi; Chen, Hongyan; Wang, Rui; Mo, Chunyu
Abstract: The salinity of groundwater in Qinzhou Bay has been increasing since 2013. This phenomenon affects livelihoods and the local agricultural economy, specifically in the Longmengang area. In this work, we investigate the causes of water salinization to provide evidence for effectively managing the local water resources and improving water quality. We collected 110 samples of water from spatially distributed local wells, rivers, reservoirs, and the sea, and conducted a hydrochemical study complemented by numerical modeling. We found that water pumping and mariculture practices are the principal contributors to seawater intrusion into the groundwater table, which leads to increased water salinization. Plain Language Summary: Groundwater salinity in Qinzhou Bay is increasing due to excessive well water extraction and mariculture practices, which promote seawater intrusion into the local groundwater table. Based on the hydrochemical analyses, the spatially distributed trend of ions content in groundwater shows low concentrations inland and increasing concentrations seaward. However, several localities of Qinzhou Bay are out of this scenario because of artificial activities requiring specific monitoring and regulation. Key Points: Field investigations and hydrochemical analyses show salinization of groundwater in Qinzhou Bay Hydrogeological modeling indicates that different processes contribute to water salinization Groundwater salinization in Longmen Island is caused by excessive groundwater use and mariculture practices